Penerapan Metode Forward Chaining dan Certainty Factor untuk Mendiagnosa Penyakit Sapi Perah Berbasis Android - Mahendra, Wahyu Eka; Andryana, Septi; Winarsih, Winarsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Dairy cows are suitable livestock to be developed because they can produce milk as a source of beneficial protein for the body. One of the obstacles faced by farmers is the emergence of diseases in dairy cows such as mastitis. Often breeders feel confused about the illnesses their pets suffer; this is due to their lack of insight into the types of diseases of dairy cows. In this study, a solution was provided, namely providing a service by applying the forward chaining method and certainty factor in an Android-based expert system application. This study aims to broaden farmers’ insight, as well as help breeders to facilitate faster, more practical initial diagnosis and treatment solutions. The results of this study indicate that, in calculating the sample, the diagnosis of mastitis has a confidence level of 99.92%. This number shows that this system can be applied to solve existing problems.